Verification and validation of a CFD model for simulations of large-scale compartment fires - Suard, S.; Lapuerta, C.; Babik, F.; Rigollet, L. (Nuclear engineering and design, 2011)
► In this work the famous V&V process is adapted to a fire field model. ► Analytical, manufactured and benchmark solutions are used for the verification phases. ► The validation process is performed with a building-block approach in order to divide the complexity of an engineering system. ► Comparison with an large-scale fire scenario is done. A fire field model is being developed at IRSN to simulate a fire in mechanically ventilated compartments. This numerical tool has the specificity of being one of the rare fire field model that allows us determination of over or underpressure peaks and reverse flow in intake ducts of the ventilation network. Although dedicated to fire simulations in confined environments, the ISIS computer code is a field model, also called CFD model, and thus enables to simulate many academic and industrial flows. The assessment process of such a numerical tool is a complex task and requires a suitable methodology. The purpose of this paper is therefore to outline an adaptation of the wellknown V&V method applied to the verification and validation processes of a fire field model. Numerical methods and physical models used in the code are briefly presented first. Afterwards, the verification and validation phases of the fire field model dealt with and exhibit comparisons to analytical, manufactured or benchmark solutions for the verification phase and the development of a building-block approach for the validation phase. For these two V&V phases, an example is clearly described in detail: the first illustrates a test case from the verification matrix while the second refers to a complete system from the validation process and describes a fire simulation in a large-scale compartment mechanically ventilated. The results, in good agreement with the experimental measurements show that the code is validated for these types of fire scenarios.